Students’ Responses to the Comic based on the Local Potential of West Kalimantan on Biodiversity Material 10 th Grade of MAN 2 Pontianak - Sari, Eka; Yeni, Laili Fitri; Yuniarti, Anisyah (UIN Fatmawati Sukarno Bengkulu, 2022)
Comics are one instance of visual media that can be used as learning media. Comics engage students to be more interested, motivated, and entertained so that they can help teachers deliver learning materials. The comics developed in this study contain material about the biodiversity that exists in West Kalimantan, especially endemic flora and fauna, considering that West Kalimantan has various potential for diversity. This study aims to determine the feasibility of comics based on the local potential of West Kalimantan on biodiversity material as a learning medium for class X MAN 2 Pontianak and to determine student responses to the developed learning media. The form of this research is descriptive with a survey research method. The sample in this study was class X MIA 4 MAN 2 Pontianak which was selected through a purposive sampling technique. The instruments used were comic media validation sheets and student response questionnaires. Based on the results of the validation data analysis, the calculation of the CVR and CVI values against the 11 assessment indicators, it was found that the comic media developed was categorized as valid with the CVR and CVI values by 1. The results of student responses to the developed comic media, for 3 aspects including cognitive, affective, and conative is 76.18% with a high category. Cognitive responses of 77.6%, affective responses of 78.3%, and conative responses of 72.66% with a high category, respectively. Therefore, comic media based on local potential of flora and fauna endemic to West Kalimantan is feasible to be used as a learning medium in class X in MAN 2 Pontianak, and student responses to the developed media are categorized as strong responses.